Futebol: um desporto também delas - Ana Cláudia Meireles Cerqueira (2019)
The present work aims to serve as a professional internship report to qualify for the Master's Degree in High Performance Training by the Faculdade de Desporto da Universidade do Porto. My main objectives are to show a bit of the reality of women's football and describe in an organised and categorised way, my own experience as a trainer in the sub-19 team (Ribeirão 1968 Futebol Clube). I will ponder on the difficulties, problems and main events of this experience as well as the strategies I chose to adopt forming a summary of my responsibilities, effort and dedication. The report is divided into six segments: introduction, personal context, context of practice, practice, development of professional practice and lastly my conclusions and expectations for the future. I will start by making a brief introduction to the subject. I will continue by relaying my life journey up to this moment and my personal expectations of the professional internship. In the third section I will characterize the Club and the athletes and address a few key aspects of my experience. The fourth segment will focus on the sub-19 team of the RFC and my work with them. Lastly, I will reflect on my year as an intern trainer and try to envision my professional objectives.